Policy on the Use of Augmented Reality (AR) Technology in Learning: Opportunities and Challenges - Deding Ishak (Sean Institute, 2025)
The development of digital technology has driven a transformation in the education system, one of which is through the use of Augmented Reality (AR) technology in the learning process. AR enables the integration of virtual objects into real environments, thereby enhancing interactivity, conceptual understanding, and student engagement. However, the implementation of AR in learning is inseparable from policy aspects that regulate infrastructure readiness, educator competency, curriculum, as well as ethical aspects and equitable access to technology. This study aims to analyze the policy of using Augmented Reality technology in learning by examining the opportunities and challenges faced in its implementation. The research method used is a qualitative approach with a literature review of various regulations, educational policies, and relevant previous research findings. The results indicate that the use of Augmented Reality (AR) technology in learning has significant potential to improve the quality of learning through the visualization of abstract concepts, increased engagement and motivation to learn, experiential learning, personalized materials, and strengthened student collaboration. AR can create a more interactive, contextual, and meaningful learning experience, thus supporting conceptual understanding and the development of 21st-century skills. However, AR implementation still faces various challenges, such as high costs, disparities in technology access, limited digital literacy, technology dependency, curriculum and content readiness, and potential health impacts. Therefore, AR utilization needs to be supported by appropriate policies, infrastructure, and pedagogical strategies for effective, equitable, and sustainable implementation within the education system.